Sexually aggressive children : coming to understand them - Araji, Sharon (Sage Publications, 1997)
Accessible and sensitive, this book provides a comprehensive overview of sexual abuse perpetrated by children 12 years old and younger. Drawing attention to this frequently overlooked population, the author explores the familial, extrafamilial and situational factors conducive to various types of sexual abuse by children so young. For professionals and researchers having to consider sexually aggressive acts by children as young as two or three, this book examines the theories and frameworks used to explain this kind of behaviour, and outlines their associated social and psychological characteristics. Sharon KAraji identifies nine programmes and practices designed by therapists treating individuals, families and groups dealing with preadolescent sexually aggressive behaviour, and concludes with an assessment of the reporting and investigation of cases.